Penguatan Sinergi Pemerintah dan Masyarakat dalam Pengembangan UMKM Pariwisata Pantai Berbasis Digital untuk Meningkatkan Daya Saing Ekonomi Lokal - Adit Setyawan; Nia Maysarah; Ayu Syahirah; Lola Widyana Binti Yunaidi; Ahmat Riduan; Al Usma Sulis; Rifa Felisa Yuda; Zainal Zainal; Fatimah Nur Khovivah; Hutri Agus Romi; Lukman Hakim (Institut Teknologi dan Bisnis Semarang, 2026)
Tok Anjang Beach, located in Batu Besar Village, Nongsa District, Batam City, is a coastal tourism destination that serves as an economic backbone for surrounding Micro, Small, and Medium Enterprises (MSMEs), particularly those engaged in culinary products, local snacks, and chalet rental services. The problems faced include conventional marketing practices, low adoption of digital transactions, and suboptimal synergy between business actors and local government. This study aims to describe the synergy between the Department of Industry and Trade (Disperindag) of Batam City and the MSME community around Tok Anjang Beach in encouraging the digitalization of coastal tourism businesses to strengthen local economic competitiveness. A descriptive qualitative approach was employed through a Community Service Program (KPM), with data collected through observation, interviews, and direct mentoring of MSME actors. The results show that collaborative mentoring, including digital marketing training, business registration number (NIB) facilitation, QRIS payment adoption, and digital product catalog development, successfully increased business visibility, expanded market reach, and fostered greater awareness among MSME actors of the importance of digital transformation in strengthening the competitiveness of coastal-tourism-based local economies.